Titanic [videorecording] - Cameron, James; Landau, Jon.; Sanchini, Rae. ([S.l.] Paramount Pictures Corporation and Twentieth Century Fox for Film Corporation, 1997)
A story of young lovers who find each other on the maiden voyage of the R.M.S. Titanic. But when the doomed luxury lines collides with an iceberg in the frigid North Atlantic, their passionate love affair becomes a thrilling race for survival.
VHS.
Leonardo DiCaprio as Jack and Kate Winslett as Rose.
Winner of 11 Academy Awards.
Keywords: Titanic (Steamship).; Feature films; Shipwrecks -- North Atlantic Ocean